Tingkat Kepuasan Pasien BPJS dan Pasien Umum - Riska Yanuarti; Eva Oktavidiati; Henni Febriawati; Oktarianita Oktarianita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the difference in satisfaction of BPJS patients and general patients at the Betungan Health Center, Bengkulu City. This research is a descriptive study with a cross-sectional design. The results of the BPJS patient satisfaction study were 20 respondents (50%) were satisfied. General patient target as many as 21 respondents (52.5%) was satisfied. The results of statistical tests obtained p-value satisfaction of BPJS patients and general patients based on tangible dimensions <0.05 (p=0.025), reliability dimension (p=0.001), responsiveness dimension (p=0.001), assurance dimension (p=0.001) and empathy dimension (p=0.001). In conclusion, there are differences in the satisfaction of BPJS patients and general patients at the Betungan Health Center, Bengkulu City. Keywords: BPJS, General Patients